2008
DOI: 10.1155/2008/523081
|View full text |Cite
|
Sign up to set email alerts
|

Cord Blood Ischemia‐Modified Albumin Levels in Normal and Intrauterine Growth Restricted Pregnancies

Abstract: Ischemia-modified albumin (IMA) is a sensitive biomarker of cardiac ischemia. Intrauterine growth restriction (IUGR) may imply fetal hypoxia, resulting in blood flow centralization in favour of vital organs (brain, heart, adrenals—“brain sparing effect”). Based on the latter, we hypothesized that cord blood IMA levels should not differ between IUGR and appropriate-for-gestational-age (AGA) full-term pregnancies. IMA was measured in blood samples from doubly-clamped umbilical cords of 110 AGA and 57 asym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 34 publications
1
28
2
Order By: Relevance
“…Iacovidou et al reported that IMA levels in cord blood were increased in cases of elective cesarean section compared to cases of vaginal delivery. 28 In our study, an upward trend was observed at the level of IMA in newborns from cesarean section, although the difference between the groups was not significant. These results might be influenced by the relatively small sample size, especially in cases of cesarean section.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Iacovidou et al reported that IMA levels in cord blood were increased in cases of elective cesarean section compared to cases of vaginal delivery. 28 In our study, an upward trend was observed at the level of IMA in newborns from cesarean section, although the difference between the groups was not significant. These results might be influenced by the relatively small sample size, especially in cases of cesarean section.…”
Section: Discussioncontrasting
confidence: 62%
“…Differently, in a previous study, Iacovidou et al did not find any difference in cord blood IMA levels between non-distressed IUGR and appropriate for gestational age neonates at term. 28 These conflicting results may be attributed to the fact that, in our study, the complicated pregnancy group did not encompass only IUGR cases. Also the authors explained their results without any evidence of myocardial damage in nondistressed term IUGR neonates.…”
Section: Discussionmentioning
confidence: 73%
“…This significant difference in IMA, however, was not observed at 6 or 24 h after birth. In the Iacovidou et al 37 study, no significant difference in cord blood IMA was seen between IUGR and appropriate for gestational age (AGA) neonates. In that study, however, only 13 of 57 IUGR neonates were born to mothers with PE, whereas, in the present study, 10 of 11 SGA neonates were born to mothers with PE.…”
Section: Discussionmentioning
confidence: 90%
“…This significant difference in IMA, however, was not observed at 6 or 24 h after birth. In the Iacovidou et al …”
Section: Discussionmentioning
confidence: 99%
“…It has not been assessed in pregnant women because of the lack of data on physiologic changes of IMA in pregnancy. Moreover, a PubMed search extending over the time period from 1975 to October 2008 using the keywords ‘ischemia‐modified albumin’ and ‘pregnancy’ revealed only five studies in the available English literature (4, 5), (10–12).…”
Section: Discussionmentioning
confidence: 99%